20.9k views
1 vote
Solve for x 3(-x-3)+x-3=26

2 Answers

5 votes

Answer:


\boxed {x = -19}

Explanation:

Solve for the value of
x:


3(-x - 3) + x - 3 = 26

-Use Distributive Property:


3(-x - 3) + x - 3 = 26


3(-x ) - 9 + x - 3 = 26

-Combine both
-9 and
3:


3(-x ) - 9 + x - 3 = 26


3(-x ) - 12 + x = 26

-Add
12 to both sides:


3(-x ) - 12 + 12 + x = 26 + 12


3(-x) + x = 38

-Multiply the
-1 by
3:


3(-x) + x = 38


-3x + x = 38

-Combine both the
-3x and
x:


-3x + x = 38


-2x = 38

-Divide both sides by
-2:


(-2x)/(-2) = (38)/(-2)


\boxed {x = -19}

Therefore, the value of
x is
-19.

User Jagajit Prusty
by
5.5k points
4 votes


\bold{Hello!}\\\bold{Your~Answer~Is~Below!}

______________________________


\bold{Solution~Steps:}

When we have a problem with parenthesis we must use distributive property:


  • 3 ×
    -x-3
  • The
    3 cancels out, leaving
    -x

*
3(-x)-9+x-3=26

Subtract
3 from
-9:


  • 3-(-9)=-12

*
3(-x)-12+x=26

Add
12 to both sides:

  • Since
    -12 is negative we do the opposite of what we see, so it cancels out.

  • -12+12= Cancels out

  • 26+12=38

*
3(-x)+x=38

Multiply
3 and
-1:

  • In this case we have
    2 x's, so we need to get rid of one. We do this by turning
    (-x) into
    -1.
  • Then we multiply them together:
    3 ×
    -1=-3

*
-3x+x=38

Combine like terms:


  • -3x+x=-2x

*
-2x=38

Divide to get
x alone:

  • Divide by
    -2 on each side by rule of opposites:
    -2x ÷
    -2=x

  • 38 ÷
    -2=-19


\boxed{x=-19}

______________________________


\bold{Hope~this~helps,}\\\bold{And~best~of~luck!}\\\\\bold{~~~~~~-TotallyNotTrillex}

User Ubeogesh
by
5.0k points